Challenges in the Implementation of the Kurikulum Merdeka at a Senior Secondary School: Perspectives of Experienced and Inexperienced English Teachers - Faisal; Hanifah, Lulu (Institut Agama Islam Negeri Palopo, 2025)
This study investigated challenges in implementing Kurikulum Merdeka at the senior secondary school level, focusing on teaching English in the Curriculum 2013 and Kurikulum Merdeka (KM). It used document analyses to examine relevant curriculum documents and identify English teachers in Indonesia. It used in-depth semi-structured interviews to gain insights into two experienced and two inexperienced English teachers' challenges when implementing KM. The findings suggest that, notwithstanding their lengths of teaching experience, the teachers from both groups had similarities and differences regarding their reported challenges when they implemented KM. In terms of the similarities, their replies primarily focused on learning time and students’ reluctance towards learning English. They, however, had some prominent differences. The experienced teachers asserted more challenges in managing student-centered learning when learning and found it difficult to combine English subjects with other subjects. This study contributes to a better understanding of the implementation of KM in senior secondary schools. It provides valuable insights for English teachers and educators implementing the KM. It finally recommends that professional development programs emphasize enhancing teachers’ knowledge and competencies in applying student-centered learning activities and providing more teaching practice rather than administration management.